Has physical therapists’ management of musculoskeletal conditions improved over time? - Zadro, Joshua R. (Braz J Phys Ther, 2020)
BACKGROUND: Our 2019 systematic review found that up to 63% of physical therapists provided recommended care for musculoskeletal conditions, up to 43% provided non-recommended care, and up to 81% provided care of unknown value. We included studies published as early as 1993 and as recent as 2017. OBJECTIVE: To determine whether physical therapists’ treatment choices for musculoskeletal conditions have improved over time. METHODS: For the original review, we included studies (until April 2018) that quantified physical therapy treatment choices for musculoskeletal conditions through surveys of physical therapists, audits of clinical notes, and other methods (e.g. clinical observation). Using medians and interquartile ranges, we summarised the percentage of physical therapists who provided treatments that were recommended, not recommended, and of unknown value. For this analysis, we stratified the findings from the above systematic review by decade (1990–1999, 2000–2009, 2010–2018). RESULTS: The median percentage of physical therapists who provided recommended treatments (40% from 1990 to 1999, 50% from 2000 to 2009, and 35% from 2010 to 2018) and non-recommended treatments (41%, 28%, and 39% respectively) has not changed over time. However, more physical therapists seem to be providing treatments of unknown value (41% from 1990 to 1999, 55% from 2000 to 2009, and 70% from 2010 to 2018). CONCLUSION: Possible explanations for this trend include the growing need for clinical innovation, challenge of keeping up to date with evidence, increased exposure to treatments of unknown value, belief that evidence is not relevant to practice, and possible limitations of the data. Strategies to help physical therapists replace non-recommended care with recommended care are discussed.